2016
DOI: 10.1007/s00213-016-4397-4
|View full text |Cite
|
Sign up to set email alerts
|

Cannabigerol is a novel, well-tolerated appetite stimulant in pre-satiated rats

Abstract: RationaleThe appetite-stimulating properties of cannabis are well documented and have been predominantly attributed to the hyperphagic activity of the psychoactive phytocannabinoid, ∆9-tetrahydrocannabinol (∆9-THC). However, we have previously shown that a cannabis extract devoid of ∆9-THC still stimulates appetite, indicating that other phytocannabinoids also elicit hyperphagia. One possible candidate is the non-psychoactive phytocannabinoid cannabigerol (CBG), which has affinity for several molecular targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 47 publications
(76 reference statements)
0
51
1
2
Order By: Relevance
“…All groups n = 16, * p < 0.05, ** p < 0.01. † Data for purified CBG has been previously published (Brierley et al 2016a), and is reproduced here for comparison with CBG-BDS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All groups n = 16, * p < 0.05, ** p < 0.01. † Data for purified CBG has been previously published (Brierley et al 2016a), and is reproduced here for comparison with CBG-BDS.…”
Section: Resultsmentioning
confidence: 99%
“…Although determining the mechanism of action for this hyperphagia was beyond the scope of these studies, we have previously speculated on putative mechanisms based on the published in vitro affinities and activities of CBG (Brierley et al 2016a). In light of the apparent greater potency of CBG-BDS, such speculation can be extended based on the differential affinities and activities reported in comparative in vitro studies of the purified and BDS forms (De Petrocellis et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to Δ 9 ‐THC, there are now known to be over 100 other phytocannabinoids in C. sativa , the majority of which are non‐psychoactive, some of which have appetite‐modulating effects . We have recently shown that cannabigerol (CBG), a non‐psychoactive phytocannabinoid, increases food intake in healthy rats without eliciting neuromotor side effects . Given that patients undergoing chemotherapy commonly report appetite loss, altered food palatability, and early satiety, CBG may have potential to attenuate these anorectic side effects.…”
Section: Introductionmentioning
confidence: 99%